Islamic Finance Tools as an Alternative to Prevent Future Global Crises - Trenovski, Borce; Merdzan, Gunter; Kozheski, Kristijan (Pazıl Reklam, Danışmanlık, Matbaa ve Organizasyon, 2019)
The Islamic economy, although with a long tradition and application, finally got its five minutes in terms of the Global Economic Crisis, at a time when the basic postulates of the neoliberal conception fell into a crisis and showed that individual/personal interest, deregulation and financial innovations developed over the years are particularly vulnerable to financial shocks and economic crises. When it comes to Islamic economy it is inevitable to elaborate Islamic finance as one of the fastest growing segments of the global financial industry with global funds expected to exceed $ 3 trillion by 2020. They have become increasingly relevant to financing development, also in non-Muslim countries. In order not to be caught in another crisis that will result in a much larger scale, important changes are needed to eliminate injustice and inequality in financial affairs and to provide discipline to the financial system. In this respect, the financial instruments offered by the Islamic financial system, where ethical rules stand out, appear to be an alternative to what traditional banks offer. One of the main reasons, why in number of research Islamic finance instruments are offered as an alternative to traditional instruments, according our hypothesis is that most of the activities that triggered the 2008 Global Financial Crisis are not in the Islamic financial system implemented under Islamic rules. The paper will elaborate first the financial architecture concerning Global Economic Crisis, as well as financial alternatives to some of the main drivers of the last Global Crisis. As alternatives to conventional financial instruments the following financial instruments representative of Islamic financial system, will be further analyzed: Mudaraba, Murabaha, Musharaka, Ijara, Bay Al-Salam, Sukuk, etc.
Keywords: Global financial crisis 2008; moral deprivation; derivative products; Islamic finance tools